A Longitudinal Investigation of the Importance of Course Subjects in the Hospitality Curriculum: An Industry Perspective. Issue 1 (2nd January 2016) - Min, Hyounae; Swanger, Nancy; Gursoy, Dogan
ABSTRACT: Utilizing a longitudinal approach, this study examines the importance of course subjects in hospitality curriculum from the perspective of the industry professional and identifies changes in the importance of course subjects over the last 10 years using data collected in 2004, 2009, and 2014. Findings suggest that internship/industry experience, preparation for industry employment, leadership, hospitality management and organization, and ethics have been consistently ranked as the most important top five course subjects by industry professionals during the last 10 years. This study identifies a number of course subjects that have been decreasing in importance for the industry and a number of course subjects that have emerged as critical course subjects over time. The most important factor in developing a curriculum that ensures graduates' success in their career is the hospitality program's ability to deal with change. Suggestions and implications for hospitality programs are provided.